Amyloid‐induced β‐cell dysfunction and islet inflammation are ameliorated by 4‐phenylbutyrate (PBA) treatment. Issue 12 (15th August 2017) - Montane, Joel; de Pablo, Sara; Castaño, Carlos; Rodríguez‐Comas, Júlia; Cadavez, Lisa; Obach, Mercè; Visa, Montse; Alcarraz‐Vizán, Gema; Sanchez‐Martinez, Melchor; Nonell‐Canals, Alfons; Parrizas, Marcelina; Servitja, Joan‐Marc; et al.
ABSTRACT: Human islet amyloid polypeptide (hIAPP) aggregation is associated with β‐cell dysfunction and death in type 2 diabetes (T2D). we aimed to determine whether in vivo treatment with chemical chaperone 4‐phenylbutyrate (PBA) ameliorates hIAPP‐induced β‐cell dysfunction and islet amyloid formation. Oral administration of PBA in hIAPP transgenic (hIAPP Tg) mice expressing hIAPP in pancreatic β cells counteracted impaired glucose homeostasis and restored glucose‐stimulated insulin secretion. Moreover, PBA treatment almost completely prevented the transcriptomic alterations observed in hIAPP Tg islets, including the induction of genes related to inflammation. PBA also increased β‐cell viability and improved insulin secretion in hIAPP Tg islets cultured under glucolipotoxic conditions. Strikingly, PBA not only prevented but even reversed islet amyloid deposition, pointing to a direct effect of PBA on hIAPP. This was supported by in silico calculations uncovering potential binding sites of PBA to monomeric, dimeric, and pentameric fibrillar structures, and by in vitro assays showing inhibition of hIAPP fibril formation by PBA. Collectively, these results uncover a novel beneficial effect of PBA on glucose homeostasis by restoring β‐cell function and preventing amyloid formation in mice expressing hIAPP in β cells, highlighting the therapeutic potential of PBA for the treatment of T2D.—Montane, J., de Pablo, S., Castaño, C., Rodríguez‐Comas, J., Cadavez, L., Obach, M., Visa, M., Alcarraz‐Vizán, G., Sanchez‐Martinez, M., Nonell‐Canals, A., Parrizas, M., Ser‐vitja, J.‐M., Novials, A. Amyloid‐induced β‐cell dysfunction and islet inflammation are ameliorated by 4‐phenylbutyrate (PBA) treatment. FASEB J. 31, 5296–5306 (2017). www.fasebj.org